2013
DOI: 10.1021/jo401856r
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nonadiabatic Reactions: Ring-Opening 4,6-Dimethylidenebicyclo[3.1.0]hex-2-ene Derivatives to Aromatic Reactive Intermediates

Abstract: Potential singlet-triplet surface crossings for the ring opening of 4,6-dimethylidenebicyclo[3.1.0]hex-2-ene derivatives were explored using density functional theory (DFT) and complete active space self-consistent field (CASSCF) methods. Since these ring openings involve relatively high energy species that lead to relatively stable aromatic species, a good scenario for potential nonadiabatic events, we posited that the reaction paths of these ring openings might come close to or cross excited state surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…In a follow-up to their 1999 study, Carpenter and co-workers concluded in 2005 that allene-ene-yne cyclization also involves a post-transition state conical intersection that allows access to both zwitterion and the diradical intermediates . In 2013, Stumetz, Nadeau, and Cremeens described calculations (CASSCF and DFT) on the ring-opening of 4,6-dimethylidenebicyclo[3.1.0]­hex-2-ene derivatives to form bis-benzyl diradical intermediates (Scheme , bottom), predicting that post-transition state crossings between the singlet and triplet surfaces occur for these reactions . Related “two-state reactivity” has been described for inorganic reactions involving transition metals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up to their 1999 study, Carpenter and co-workers concluded in 2005 that allene-ene-yne cyclization also involves a post-transition state conical intersection that allows access to both zwitterion and the diradical intermediates . In 2013, Stumetz, Nadeau, and Cremeens described calculations (CASSCF and DFT) on the ring-opening of 4,6-dimethylidenebicyclo[3.1.0]­hex-2-ene derivatives to form bis-benzyl diradical intermediates (Scheme , bottom), predicting that post-transition state crossings between the singlet and triplet surfaces occur for these reactions . Related “two-state reactivity” has been described for inorganic reactions involving transition metals .…”
Section: Introductionmentioning
confidence: 99%
“…14 In 2013, Stumetz, Nadeau, and Cremeens described calculations (CASSCF and DFT) on the ring-opening of 4,6-dimethylidenebicyclo[3.1.0]hex-2-ene derivatives to form bis-benzyl diradical intermediates (Scheme 2, bottom), predicting that post-transition state crossings between the singlet and triplet surfaces occur for these reactions. 15 Related "two-state reactivity" has been described for inorganic reactions involving transition metals. 16 We wondered whether similar post-transition state surface crossings were occurring in the Brummond−Chen cyclizations we had examined previously (Scheme 1d).…”
Section: ■ Introductionmentioning
confidence: 99%